Infarct Size and Long-Term Clinical Outcomes of Prasugrel versus Clopidogrel in Patients with Acute Coronary Syndrome Undergoing Coronary Artery Stenting: A Prospective Randomized Study - Yabe, Takayuki; Noike, Ryota; Okubo, Ryo; Amano, Hideo; Ikeda, Takanori (International Journal of Angiology, 2022)
The antiplatelet drug prasugrel inhibits platelet aggregation early after oral administration. This study examined whether prasugrel is effective in inhibiting infarct size and can reduce the incidence of major adverse cardiovascular events (MACE) in patients with acute coronary syndrome (ACS). This study was a single-center, prospective, randomized pilot study. Among 80 ACS patients treated at our institution between August 2014 and September 2015, 76 ACS patients who underwent stenting and achieved thrombolysis in myocardial infarction flow grade 3 were assigned to receive aspirin plus prasugrel (prasugrel group; n = 37) or aspirin plus clopidogrel (clopidogrel group; n = 39). The primary endpoint was survival free of MACE. The secondary endpoint was the evaluation of infarct size defined as the area under the curve (AUC) of troponin I, calculated using the linear trapezoidal method. During follow-up (mean, 1262.4 ± 599.6 days), 14 patients showed MACE. No significant differences in CYP2C19 genotype were seen between groups. AUC of troponin I up to 72 hours after intervention tended to be smaller in the prasugrel group (1,927.1 ± 2,189.3 ng/mL) than in the clopidogrel group (3,186.0 ± 3,760.1 ng/mL, p = 0.08). Cumulative incidence of MACE was significantly higher in the clopidogrel group (log-rank test; p = 0.02). Compared with clopidogrel, prasugrel was associated with reduced infarct size and lower frequency of long-term outcomes among ACS patients undergoing stenting.
Keywords: antiplatelet drug; prasugrel; acute coronary syndrome; percutaneous coronary intervention